Women and adolescent girls’ experience with COVID-19 in rural Senegal - Dione, Malick; Lo, Codé; Seye, Moustapha; Fall, Abdou Salam; Hidrobo, Melissa; Le Port, Agnès; Heckert, Jessica; Peterman, Amber (International Food Policy Research Institute, 2021)
Senegal reported its first case of COVID-19 on March 2, 2020. The government responded within two weeks, introducing preventive measures to slow the spread of the virus, including the declaration of a public health emergency, border closures, and the prohibition of intercity travel and gatherings. These measures also slowed economic activity throughout the country and disrupted food supply chains and markets, contributing to loss of livelihoods, income, and households’ purchasing power. Evidence suggests that globally, women have been hit harder by the COVID-19 crisis, in particular with respect to impacts on economic security, health, education, and increased caretaking responsibilities in the household.